Network traffic monitoring system with approach (NTMs) / Lee Chin Han - Lee , Chin Han (2004)
Network Traffic Monitoring System (NTMs) is a standalone system that use to monitoring network traffic of computers in a LAN environment. It is capable of filtering out a certain port. IP address and protocol and generates a network traffic graph. IT behaves as a useful tool for network administrator and network engineer. This system is target to be implementing in a small organization that own LAN such as Faculty of Computer Science and Information Technology in University Malaya. It got the mission of monitoring a network, trace and identifies misuse of computer, improve network manageability and over come some network problem. Waterfall model is chosen as the methodology to develop this system. Its is hope that this technique can help and direct the development of this system in a efficient and cost effective approach. To achieve the target of monitor the network traffic the system apply combination technology of Visual Basic, Microsoft Access, WinPeap, MRTG and some relevant tools.